1998
DOI: 10.1038/sj.bjc.6690025
|View full text |Cite
|
Sign up to set email alerts
|

Three independently deleted regions at chromosome arm 16q in human prostate cancer: allelic loss at 16q24.1–q24.2 is associated with aggressive behaviour of the disease, recurrent growth, poor differentiation of the tumour and poor prognosis for the patient

Abstract: Prostate cancer is one of the most common cancers among men in many Western countries, including Finland. However, the molecular genetic events associated with the development and progression of the disease are poorly known. According to the multistep model of carcinogenesis, several genetic aberrations take place in prostate cancer, but only a few genes potentially involved in prostatic carcinogenesis have been identified.It has been suggested that genetic alterations take place in several chromosomal regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…That is, WOX1 protein may participate in inhibiting cancer cell metastasis. This notion is supported by the observations that distinct deleted regions on chromosome segment 16q23-24, encoding WWOX/FOR2/WOX1, are associated with metastases in prostate and breast cancers (Caligo et al, 1998;Elo et al, 1999;Li et al, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…That is, WOX1 protein may participate in inhibiting cancer cell metastasis. This notion is supported by the observations that distinct deleted regions on chromosome segment 16q23-24, encoding WWOX/FOR2/WOX1, are associated with metastases in prostate and breast cancers (Caligo et al, 1998;Elo et al, 1999;Li et al, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…12,25,49 Furthermore, additional sites of deletion more telomeric to 16q22 have been reported and it seems as if the long arm of chromosome 16 harbours multiple tumour suppressor genes. 12,13,25 Some of these investigators found a signi®cant correlation between 16q losses and metastatic and aggressive behaviour of prostate cancers. 11 ± 13 In the present study, allelic imbalance at 16q was not signi®cantly associated with higher Gleason scores, which is in concordance with the ®ndings by Godfrey and co-workers.…”
Section: Allelic Losses In Prostatic Cancermentioning
confidence: 99%
“…Moreover, it is increasingly evident that differing clinical behavior of histologically similar tumors is because of distinct and recurrent patterns of genomic alterations and that these may define distinct subsets of disease and thus be prognostic. [1][2][3][4] aCGH is ideally suited to delineating these genomic differences and for the development of biomarkers. However, the coupling of aCGH and clinical data for biomarker discovery and disease stratification requires patients with significant clinical follow-up, meaning that in most cases archived tumor material must be used to identify associations between copy number changes and clinical outcome.…”
mentioning
confidence: 99%